Removal of Acidic Dye from Aqueous Solution Using Surfactant Modified Bentonite (Organoclay): Batch and Kinetic Study (Journal of Engineering, 2020)
Modified bentonite has been used as effective sorbent material for the removal of acidic dye (methyl orange) from aqueous solution in batch system. The natural bentonite has been modified using cationic surfactant (cetyltrimethyl ammonium bromide) in order to obtain an efficient sorbent through converting the properties of bentonite from hydrophilic to organophilic. The characteristics of the natural and modified bentonite were examined through several analyses such as Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and Surface area. The batch study was provided the maximum dye removal efficiency of 88.75 % with a sorption capacity of 555.56 mg/g at specified conditions (150 min, pH= 2, 250 rpm, and 0.5 g/100 ml). The-results-showed that with the Freundlich isotherm model the sorption data was accurately described with (R2≥0.94) in comparison with the Langmuir model under the studied conditions. The kinetic studies were revealed that the sorption follows a pseudo-second-order kinetic model which indicates chemisorption between sorbent and sorbate molecules.